Experimental Stress Analysis 51 Selected, peer reviewed papers from the 51st Annual of the International Scientific Conference on Experimental Stress Analysis (EAN 2013), June 11-13, 2013, Litomerice, Czech Republic (Trans Tech Publications Ltd, 2013)
Collection of selected, peer reviewed papers from the 51st Annual of the International Scientific Conference Experimental Stress Analysis (EAN 2013), June 11-13, 2013, Litomerice, Czech Republic. Volume is indexed by Thomson Reuters CPCI-S (WoS).The 69 papers are grouped as follows: Chapter 1: Stress Analysis in Metal and Composites; Chapter 2: Experimental Methods and Stress Analysis in Building Materials Keyword: experimental analysis, numerical solution, stress, strain, verification, building industry, construction, deformation, biomechanics, mechanics, dynamics Scientists and engineers from across Eastern Europe explore the experimental analysis of stress in metals and composite and in building materials. The 69 papers include discussions of investigating the stress-strain state of the surface layer of machine elements made of a sintered non-uniform material, numerical and experimental research into the design optimization of baths for producing nanofibers by electrospinning, the mechanical response of the cross-linked pericardial tissue, a portable device for the indirect assessment of strength in the tension of building materials and the problem of boundary conditions, and a modified strip method to speed up the tangential stress between wheel and rail calculation. - Engineering- Materials science- Metals